(untitled) (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
The rapid development of e-commerce in Indonesia, further accelerated by the COVID-19 pandemic, has significantly reshaped consumer behavior, including in the frozen food sector. Frozen food has become a practical choice for households, while Shopee, as one of the largest marketplaces in Indonesia, provides a relevant context to examine digital marketing strategies in shaping consumer purchase intention. This study aims to analyze the influence of Influencer Endorsement, Online Customer Review, and Brand Experience on Purchase Intention, with Brand Attitude as a mediating variable. A quantitative research method was employed through a survey of Shopee users in Tangerang, and the data were analyzed using Structural Equation Modeling (SEM). The results reveal that Influencer Endorsement does not significantly affect either Brand Attitude or Purchase Intention. Conversely, Online Customer Review has a significant effect on Brand Attitude but does not directly influence Purchase Intention. Brand Experience emerges as the strongest factor, significantly influencing both Brand Attitude and Purchase Intention. Furthermore, Brand Attitude mediates the relationship between Online Customer Review and Brand Experience with Purchase Intention, but not between Influencer Endorsement and Purchase Intention. These findings highlight that in functional product categories such as frozen food, enhancing brand experience and managing customer reviews are more effective strategies than relying solely on influencer endorsements. The study contributes theoretically by emphasizing the role of Brand Attitude in digital marketing and practically by providing insights for businesses to design more impactful e-commerce strategies. Perkembangan e-commerce di Indonesia yang kian melaju pesat selama pandemi COVID-19 telah membawa perubahan signifikan terhadap perilaku konsumen, termasuk pada sektor makanan beku. Produk makanan beku menjadi pilihan praktis rumah tangga, sementara Shopee sebagai salah satu marketplace terbesar di Indonesia memberikan konteks yang relevan untuk mengkaji strategi pemasaran digital dalam membentuk niat beli konsumen. Penelitian ini bertujuan menganalisis pengaruh Influencer Endorsement, Online Customer Review, dan Brand Experience terhadap niat beli, dengan Brand Attitude sebagai variabel mediasi. Penelitian menggunakan pendekatan kuantitatif melalui survei terhadap pengguna Shopee di Tangerang. Data kemudian dianalisis dengan Structural Equation Modeling (SEM). Hasil penelitian menunjukkan bahwa Influencer Endorsement tidak berpengaruh signifikan terhadap Brand Attitude maupun niat beli. Sebaliknya, Online Customer Review berpengaruh signifikan terhadap Brand Attitude namun tidak secara langsung memengaruhi niat beli. Faktor paling kuat adalah Brand Experience, yang terbukti memengaruhi baik Brand Attitude maupun niat beli. Selain itu, Brand Attitude berperan sebagai mediator pada hubungan Online Customer Review dan Brand Experience dengan niat beli, tetapi tidak pada hubungan dengan Influencer Endorsement. Temuan ini menegaskan bahwa pada kategori produk fungsional seperti makanan beku, peningkatan pengalaman merek dan pengelolaan ulasan pelanggan lebih efektif dibandingkan sekadar mengandalkan influencer endorsement. Studi ini memberikan kontribusi teoretis terkait peran Brand Attitude dalam pemasaran digital, serta kontribusi praktis bagi pelaku usaha dalam merancang strategi e-commerce yang lebih berdampak.